Evaluation of fetal and neonatal outcomes after ingestion of Cnidium root (Cnidium officinale Makino) during pregnancy. (October 2021) - Choi, June-Seek; Han, Jung-Yeol; Koren, Gideon; Cho, Yeon-Kyung
Abstract: Cnidium officinale Makino is a perennial plant, a member of the Umbelliferae family. Cnidium root has traditionally been used as a medicinal herb. It has analgesic, antiinflammatory, antipyretic, antibacterial, antispasmodic, vasodilatory, hypertensive, and sedative effects. However, there are no studies of reproductive toxicity in humans. Therefore, this study aimed to prospectively evaluate the fetal and neonatal outcomes in the children of women who inadvertently used Cnidium root during pregnancy. In a prospective cohort study design, 111 singleton pregnant women taking Cnidium root for various reasons, and 219 age-matched singleton pregnant women unexposed to any herbal agent (unexposed group), were followed up until delivery. In the exposed group, Cnidium root was indicated as controlling cough and cold in 54.1% of patients, at the maximal dose of 12, 000 mg/day between 1 day to 12.4 weeks of gestation. Fetal outcomes, including birth weight and 1- and 5-min Apgar score, were similar for the two groups. There were four babies born with major malformations in the exposed group vs. 14 in the unexposed group (OR = 0.5; 95% CI 0.2–1.6; p = 0.190). The gestational age, length, and head circumference were relatively shorter among babies born in the exposed group. Even after adjusting for gender, there was a tenfold increase in the frequency of shorter newborns (<2SD) in the exposed group (OR = 10.1; 95% CI 1.2–87.6; p = 0.019). Our study suggests that Cnidium root is not a major human teratogen. Whether lesser gestational ages at birth and shorter birth lengths are clinically relevant after exposure to Cnidium remains to be elucidated in further studies. Highlights: The first study of exposure to Cnidium root (CR) in human There was a tenfold increase in the frequency of shorter newborns (<2SD) in the exposed group. Birth weeks were shorter in the exposed group.